The Influence of Personal Branding on Business Communications in the Digital Era - Reni Eliyanti; Novia Fetri Aliza (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2025)
The rapid advancement of digital technology has reshaped communication practices in the business sector, making personal branding an essential strategy for effective business communication on social media. This study examines the influence of personal branding on business communication in the digital era, focusing on students who actively use TikTok and Instagram. Using a quantitative approach, data were collected through an online questionnaire from students of the Islamic Communication and Broadcasting Study Program at Muhammadiyah University of Yogyakarta (academic years 2023–2024). Data were analyzed using simple linear regression with SPSS. The results indicate that personal branding has a significant effect on business communication (p = 0.020; R² = 0.179), explaining 17.9% of communication effectiveness, while the remainder is influenced by other factors. The findings highlight that uniqueness, relevance, and consistency in personal branding enhance credibility, audience trust, and business competitiveness in digital environments. Despite being limited to students and two social media platforms, this study emphasizes personal branding as a strategic communication tool for building effective and sustainable digital business relationships.